IMPACT OF DIFFERENT EXTRACTION METHODS ON PHYSICAL CHEMISTRY PROPERTIES OF PALM KERNEL OIL (ELAEISGUINEENSIS) - Ibrahim A. I.; Sarifah Nurjanah; M. Ade Moetangad Kramadibrata (Fakultas Teknologi Industri Pertanian, 2016)
This study was conducted to assess the impact of oil extraction from kernel palm by two methods of extraction they are, mechanical press and solvent (hexane) extraction. The aim of this study was to determine the impact of extraction methods on physical chemistry properties of palm Elaeisguineensis kernel oil. Methods were used for extracting oil from palm kernel according to the method of Mandal and Lee, moreover physical chemistry analysis for oils was conducted by AOAC and AOCS methods. These results showed significant differences (P<0.05) of the extraction method between five physical chemistry parameters. In these results number of saponification, peroxide, and iodine of oil that was extracted by hexane, while density was extracted mechanically and the results showed significant difference with the standards of FAO and WHO. The results showed that the number of each parameter from solvent (hexane) and mechanical press are Saponification 194.29±0.20 mgKOH/g and 215.74±1.29 mgKOH/g, Peroxide 3.72±0.25 mgKOH/g and 3.39±0.31 mgKOH/g, Iodine 18.28±0.13 mgKOH/g and 22.8±0.23 mgKOH/g, Density 0.87±0.01 g/cm3 and 0.91±0.00 g/cm3, Viscosity 27.66±1.15 mm2/s and 40.66±2.08 mm2/s, FFA 1.33±0.17% and 1.83±0.04%, respectively. The color of the oil were clear yellow by hexane extract and brown by mechanical extract. These results showed that the extraction methods of palm kernel oil by hexane is better than mechanical extraction.Keywords: Palm kernel oil, Extraction, physic-chemical properties